Improving Student Engagement in Online Chemical Engineering Classes: Using google tools to enhance collaboration and learning - Nauli, Maria Anindita (Lembaga Riset dan Inovasi Masyarakat Madani, 2025)
Online engineering education presents unique challenges in supporting student collaboration and engagement. This study looks at how Google Slides and Google Sheets can help improve collaboration and student engagement in online chemical engineering activities about process control and economic analysis. The study involved 11 students who worked together in real time using shared documents, with the instructor giving quick feedback during the activities. A questionnaire was used to collect students' opinions, and the results were analyzed using simple descriptive methods. The findings indicate that both Google Slides and Google Sheets were highly effective in fostering collaboration and enhancing the learning experience, with most students finding them user-friendly and helpful for understanding the material. This suggests that basic digital tools like Google Slides and Sheets can support better learning and teamwork in online engineering education. Future studies could explore broader applications of such tools across other technical disciplines.